Crystallisation of lead strontium titanate perovskite phase in [(Pb1-xSrx)O.TiO2]-[2SiO2. B2O3]-[K2O] glass ceramics - Sahu A.K.; Kumar D.; Parkash O. (My University, 2025)
The crystallisation of lead strontium titanate solid solution phase in glass ceramics in the [(Pb1-xSrx)O.TiO2]-[2SiO2. B2O3]-[K2O] system (x = 0. 0.1, 0.2, 0.3, 0.4) has been studied. Perovskite titanate was found to be the major phase in all samples investigated. The actual composition of the crystallites developed could not be confirmed on the basis of shifts in the XRD peak positions with changing Pb2+/Sr2+ ratio, because of similar effects due to solid solution and strain resulting from crystal clamping. Comparison of the observed intensities of the perovskite titanate phase with calculated intensities for (Pb1-xSrx)TiO3 ceramics with the same lead/strontium ratios confirmed the formation of lead strontium titanate solid solution.